Retinal microvascular alterations in children with amblyopia - Christiane Al-Haddad; Hanadi Ibrahim; Nagib Salameh; Zahi Wehbi; Dalia El Hadi; Youssef Zougheib; Ziad Bashshur (PLoS ONE, 2026)
Purpose To investigate and compare retinal vascular changes, including superficial macular vessel density, foveal avascular zone, and the macular perfusion densities, in amblyopic, fellow, and control eyes using optical coherence tomography angiography. Methods In this prospective cross-sectional study, we recruited 78 participants, including 36 with amblyopia and 42 controls, to investigate retinal parameters using optical coherence tomography angiography (OCTA) by comparing amblyopic eyes to both controls and fellow eyes. Results A total of 78 patients were enrolled, including 36 with amblyopia (mean age: 9.8 ± 4.6 years) and 42 controls (mean age: 10.0 ± 2.9 years). Among the amblyopic cohort, 18 (50%) had strabismic and 18 (50%) had anisometropic amblyopia. Baseline characteristics, including age, sex distribution, and spherical equivalent, were comparable across groups. Macular OCTA demonstrated higher outer and full macular vessel densities, as well as elevated outer and full regions perfusion densities, in amblyopic eyes relative to control. Optic disc OCTA parameters were comparable between amblyopic eyes and controls. Comparison between amblyopic and fellow eyes showed a significantly smaller macular foveal avascular zone area, with no other significant interocular differences in macular or optic disc OCTA findings. Fellow eyes and control eyes differed only in optic disc perfusion density in the outer region, which was decreased in fellow eyes. Conclusion Amblyopic eyes showed increased outer and full macular vessel and perfusion densities compared with control eyes, and a smaller foveal avascular zone area relative to fellow eyes. No significant microvascular differences were found in the optic disc OCTA among groups. These exploratory findings raise the possibility that amblyopia may be associated with subtle macular microvascular alterations, however, confirmatory studies with larger cohorts are needed.